The molecular basis of familial hypercholesterolemia in the Czech Republic: spectrum of LDLR mutations and genotype-phenotype correlations - Tichý, Lukáš; Freiberger, Tomáš; Zapletalová, Petra; Soška, Vladimír; Ravčuková, Barbora; Fajkusová, Lenka (Atherosclerosis, 2012)
BACKGROUND: Familial hypercholesterolemia (FH), a major risk for coronary heart disease, is predominantly associated with mutations in the genes encoding the low-density lipoprotein receptor (LDLR) and its ligand apolipoprotein B (APOB). RESULTS: In this study, we characterize the spectrum of mutations causing FH in 2239 Czech probands suspected to have FH. In this set, we found 265 patients (11.8%) with the APOB mutation p.(Arg3527Gln) and 535 patients (23.9%) with a LDLR mutation. In 535 probands carrying the LDLR mutation, 127 unique allelic variants were detected: 70.1% of these variants were DNA substitutions, 16.5% small DNA rearrangements, and 13.4% large DNA rearrangements. Fifty five variants were novel, not described in other FH populations. For lipid profile analyses, FH probands were divided into groups [patients with the LDLR mutation (LDLR+), with the APOB mutation (APOB+), and without a detected mutation (LDLR-/APOB-)], and each group into subgroups according to gender. The statistical analysis of lipid profiles was performed in 1722 probands adjusted for age in which biochemical data were obtained without FH treatment (480 LDLR+ patients, 222 APOB+ patients, and 1020 LDLR-/APOB- patients). Significant gradients in i) total cholesterol (LDLR+ patients > APOB+ patients = LDLR-/APOB- patients) ii) LDL cholesterol (LDLR+ patients > APOB+ patients = LDLR-/APOB- patients in men and LDLR+patients > APOB+ patients >LDLR-/APOB- patients in women), iii) triglycerides (LDLR-/APOB- patients > LDLR+ patients > APOB+ patients), and iv) HDL cholesterol (APOB+ patients > LDLR-/APOB- patients = LDLR+ patients) were shown. CONCLUSION: Our study presents a large set of Czech patients with FH diagnosis in which DNA diagnostics was performed and which allowed statistical analysis of clinical and biochemical data.
Keywords: Young Adult; Chi-Square Distribution; DNA Mutational Analysis; Gene Frequency; hodnocení rizik; genetické asociační studie; fenotyp; Male; biologické markery; mutace; Genetic Predisposition to Disease; Phenotype; Risk Assessment; Risk Factors; mladý dospělý; Biomarkers; Adolescent; Genetic Association Studies; Česká republika; Child; rozdělení chí kvadrát; hyperlipoproteinemie typ II; dítě; Adult; dospělí; mužské pohlaví; lineární modely; Receptors, LDL; mutační analýza DNA; mladiství; Czech Republic; frekvence genu; lipidy; lidé; ženské pohlaví; Humans; Apolipoproteins B; rizikové faktory; Linear Models; apolipoproteiny B; Lipids; Mutation; Hyperlipoproteinemia Type II; LDL-receptory; Female; lidé středního věku; genetická predispozice k nemoci; Middle Aged